The importance of androgen on noradrenergic responses of vas deferens isolated from acutely stressed rats - Souza, MSS; Pereira, OCM (Academic Press Ltd, 1999)
This study investigated the importance of androgen on responses to alpha and beta (norepinephrine) and alpha(1) (phenylephrine and methoxamine) agonists in vasa deferentia isolated from adult, immature, cryptorchid, and castrated rats submitted to swimming-induced acute stress. The participation of adrenergic nervous terminals was also investigated. Acute stress was shown to induce a significant subsensitivity to norepinephrine only in vas deferens from adult rats with normal levels of androgens. In addition, sympathetic denervation of the vas deferens prevented the appearance of subsensitivity. Subsensitivity was not seen when the experiments were carried out using phenylephrine and methoxamine. This shows that subsensitivity to norepinephrine in this acute stress situation may depend on other factors such as neuronal uptake, but not on alpha(1)-adrenoceptor response. Thus, when animals are exposed to acute stressogenic situations, this subsensitivity requires physiological levels of androgens to establish, and may also be involved in body homeostasis. (C) 1999 Academic Press.
Keywords: acute stress; catecholamines; androgen deprivation; denervation; rat; vas deferens